Contemporary tendencies in Colombian urban planning: the case of the 'Planes Parciales' in Medellín. Issue 4 (2nd October 2018) - Garcia Ferrari, Soledad; Smith, Harry; Calderon, Edwar
ABSTRACT: After decades of internal conflict, Colombia is experiencing economic growth and urbanization. It remains, however, one of the most socially unequal countries in Latin America. Medellín, acclaimed the most innovative city, implemented large-scale transport infrastructures to link socially excluded areas to the city; new educational and cultural facilities; new public spaces and housing projects, rooted in the Barcelona model. This so-called 'social urbanism' has shifted local perceptions, though its socio-economic impact has been questioned. This paper focuses on the less analysed transformations in planning policy and management through two instruments: the Land Use Plan (Plan de Ordenamiento Territorial – POT) and the 'Plan Parcial'. The research, based on a desktop review, interviews and site visits, examines the application of these instruments in Medellín, reflecting on how they contribute to achieving the aims of 'social urbanism'. The paper explores the differences between 'rhetoric' and practice that are reflected in those between the city's overarching plan (POT) and the implementation of 'planes parciales', focusing on redevelopment, urban renewal and urban expansion. Such differences mirror the deficiencies in the adaptation of the 'urban project' Barcelona model in Medellín, and provide the basis for a call to develop 'social urbanism' that is genuinely more socially, territorially comprehensive and inclusive.